(untitled) (Third Sector Social Economic Review, 2023)
In this study, it was aimed to investigate the occupational burnout of health personnel working in intensive care units caused by long-term work under excessive workload and stress they experience in meeting the treatment and care needs of patients requiring close treatment and follow-up. The aim and purpose of the research are to determine the effect of burnout on occupational happiness and satisfaction, since increased burnout in intensive care healthcare workers causes a decrease in work efficiency, job satisfaction and quality of care, as well as an increase in health care costs. The cross-sectional study was applied to the health personnel working in the Intensive Care Units of Bilecik Training and Research Hospital. In this study, ""Personal Information Form"", ""Maslach Burnout Scale"" and ""Vocational Satisfaction Scale"" were used as data collection tools. The answers given as a result of the questionnaires were analyzed by the researchers by entering the SPSS 15.0 program. Of the 42 participants who participated in the survey, 69% were Nurses (n=29), 14.3% were Clinical Support Staff (n=6), 11.9% were Doctors (n=5),4.8% were Medical Officer (n=2). According to MBS, the mean of Emotional Exhaustion of the participants was 20, the mean of Depersonalization was 14.28, and the mean of Decline in Personal Achievement was calculated as 17.54. No statistically significant relationship was found between the participants’ age, gender, number of children, duration of work in the intensive care unit, working hours in the intensive care unit, working overtime and monthly income, and emotional exhaustion, depersonalization and personal achievements. No significant relationship was found between the participants’ gender, education level, marital status, working hours in the intensive care unit, working hours in the intensive care unit, working overtime and their professional satisfaction. The high personal achievement score of the employees positively affects their professional satisfaction. The results of the research support the current scientific literature on the subject.